2020
DOI: 10.1007/s00402-020-03336-3
|View full text |Cite
|
Sign up to set email alerts
|

Similar revision rates in clinical studies and arthroplasty registers and no bias for developer publications in unicompartmental knee arthroplasty

Abstract: Purpose Our aim was to assess the outcome with respect to cumulative revision rates of unicompartmental knee arthroplasty (UKA) by comparing published literature and arthroplasty registry data. Our hypothesis was that there is a superior outcome of UKA described in dependent clinical studies compared to independent studies or arthroplasty registers. Methods A systematic review of all clinical studies on UKA in the past decade was conducted with the main endpoint revision rate. Revision rate was calculated as "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…This method has been commonly applied in the literature. [24][25][26]57,63,65 The exact formula for calculation is number of revisions divided by observed CYs multiplied by 100. A value of 1 revision per 100 CYs equals a 7-year revision rate of 7%, and a 10 year revision rate of 10%.…”
Section: Arthroplasty Registers and Application Ratementioning
confidence: 99%
See 1 more Smart Citation
“…This method has been commonly applied in the literature. [24][25][26]57,63,65 The exact formula for calculation is number of revisions divided by observed CYs multiplied by 100. A value of 1 revision per 100 CYs equals a 7-year revision rate of 7%, and a 10 year revision rate of 10%.…”
Section: Arthroplasty Registers and Application Ratementioning
confidence: 99%
“…However, these studies were published a decade ago and this bias has not yet been observed in other joint prostheses in recent years. 24,26,63 Therefore, the primary aim of this study was to compare current revision rates of TARs published in clinical studies of the past decade to those described in arthroplasty registers. The secondary aim was to compare revision rates between sponsored/dependent and independent studies and between mobile bearing TARs (MB-TARs) and fixed bearing TARs (FB-TARs).…”
Section: Introductionmentioning
confidence: 99%
“…The revision outcome was assessed using two methods; first, the raw number of revisions (incident) was calculated to compare between both age groups. Additionally, for the annual revision rate, revisions per 100 observed component years (CY) was adopted [ 11 ]; a widely accepted method in orthopedic literature and is used to overcome inconsistencies in data sources and follow-up periods across studies and ensure appropriate weighting in comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…The final search date was 20 September 2021. This method is widely accepted and has been applied repeatedly in the field of orthopedics concerning the use of arthroplasty registers [ 12 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%